Nano-seeding catalysts for high-density arrays of horizontally aligned carbon nanotubes with wafer-scale uniformity - Ying Xie; Yue Li; Zhisheng Peng; Chengyu Wang; Zanlin Qiu; Xinyi Cai; Tinglu Song; Jia Si; Xiaoxu Zhao; Liu Qian; Ziqiang Zhao; Jin Zhang (Nature Communications)
Abstract In the realm of modern materials science, horizontally aligned carbon nanotube arrays stand as promising materials for the development of next-generation integrated circuits. However, their large-scale integration has been impeded by the constraints of current fabrication techniques, which struggle to achieve the necessary uniformity, density, and size control of carbon nanotube arrays. Overcoming this challenge necessitates a significant shift in fabrication approaches. Herein, we present a nano-seeding method that revolutionized the preparation of catalyst nanoparticles, crucial for carbon-nanotube-array synthesis. Our approach, underpinned by ion implantation and substrate processing, allows for precise control over catalyst formation. Further development of a vertical spraying chemical vapor deposition system homogenizes the gas flow and ensures the uniform growth of carbon nanotube arrays. This nano-seeding method culminates in the direct growth of one-inch carbon-nanotube-array wafers with the highest density of 140 tubes μm−1. The high density and uniformity of the as-prepared carbon-nanotube-array wafers are validated through an advanced high-throughput characterization technique. The electrical properties of high on-state current, high on/off ratio and low subthreshold swing are demonstrated in field-effect transistors based on the arrays. This study propels the scalability of carbon-nanotube-array fabrication for future carbon-based electronics.